2019
DOI: 10.36094/scienceandculture.v85.2019.mandal.281
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of DTPAextractable micronutrients and its correlation with soil properties in selected soil profiles of Birbhum District of West Bengal

Abstract: The present study was undertaken to assess the vertical distribution of DTPA-extractable micronutrients viz. zinc, copper, iron and manganese in relation to soil properties in five selected soil profiles, one each from Sainthia, Suri II, Rampurhat II, Md Bazar and Nalhati I block of Birbhum district of West Bengal. Collected soil samples were analysed for pH, electrical conductivity, organic carbon, textural class (% sand, silt, clay) and DTPA-extractable micronutrients using standard analytical methods. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…However, at higher CaCO3 content manganese is precipitates into MnCO3 that will reduce the Mn availability for the plants. The similar results were also reported earlier by Tisdale et al [17], Meena et al [18], Meena and Mathur [19] and Mandal et al [20].…”
Section: Discussionsupporting
confidence: 91%
“…However, at higher CaCO3 content manganese is precipitates into MnCO3 that will reduce the Mn availability for the plants. The similar results were also reported earlier by Tisdale et al [17], Meena et al [18], Meena and Mathur [19] and Mandal et al [20].…”
Section: Discussionsupporting
confidence: 91%
“…The presence of Mn-bearing parent materials might also be responsible for this. Comparable outcomes were also documented by Singh et al [13], Mandavgade et al [19] and Sunandana et al [17]. According to Jain et al [20], the concentration of DTPA extractable micronutrients (iron, manganese, copper, and zinc) was highest in forest soil and at a depth of 0-15 cm and dropped as soil depth increased.…”
Section: Status Of Dtpa-extractable Cationic Micronutrientsmentioning
confidence: 59%
“…The production of insoluble Mn-oxides at higher pH values may be the cause of the negative association between accessible manganese and soil pH. The outcomes of Patel et al [24], Sunandana et al [17], and Manasa et al [25] are in good accord with these findings. There was a strong and positive connection between the DTPAextractable manganese and iron (0.29**).…”
Section: Correlation Between Dtpaextractable Cationic Micronutrients ...mentioning
confidence: 63%
See 1 more Smart Citation
“…Lakshmi et al (2021) reported that the major concern in human diets is the adequacy in grain Zn in staple food crops like rice and wheat. Zn deficiency appears as a major threat for the human population whose staple food is rice (Stein, 2010;Mandal & Ghosh, 2020). The sustainable strategy to solve the problem of Zn deficiency in humans is to enhance grain Zn concentration in staple food crops (Haider et al, 2021;Khampuang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%